IMPLEMENTASI MEDIA CERITA RAKYAT JAMBI DALAM PEMBELAJARAN AKIDAH AKHLAK TERHADAP PEMBENTUKAN KARAKTER RELIGIUS DAN MORAL PESERTA DIDIK DI MADRASAH TSANAWIYAH NEGERI 3 KOTA JAMBI - Aulia Nur, Mikha; Fadhil, M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the still low religious and moral character of some students in the study of Akidah Akhlak. This research aims to describe the implementation of Jambi folk tales media, identify religious and moral values in the story of Orang Kayo Hitam, and analyze its influence on the character formation of students at MTs Negeri 3 Kota Jambi. The research uses a qualitative approach with a case study type. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model. The research results show that the use of folk tales media is applied systematically and is able to enhance the activity, interest, and understanding of students toward religious and moral values. The values found include faith, trust in God, honesty, courage, responsibility, and social concern. In addition, students show more positive behavioral changes in their daily lives. Thus, the Jambi folktale media is effectively used in the teaching of Akidah Akhlak to shape the religious and moral character of the students.